O ato de ensinar Ciências: limites e possibilidades da prática pedagógica em sua relação com as diferentes concepções de práxis - Madureira, Cristiane Aparecida (2019)
The present study had as object of study the teaching of Nature Science teachers from São Paulo state public school, located in the Sorocaba Teaching Board, within the limits and possibilities of the pedagogical practice in its relation with different praxiological nuances. It aimed to investigate the praxis developed by these teachers, articulating them in the Marxist praxic dimensions. The theoretical framework permeated three authors who conceptualized praxis in Marx's concept: Vázquez who conceptualized praxis as conscious and oriented human activity; Lefebvre who brings to praxis the refinement of his subjectivities in reproductive, mimetic and transformative dimensions, and Freire, who understands the educational process as transformative, inherent in an authentic praxis. The data obtained were verified through a qualitative approach, in a group of 10 participating teachers. In this sample universe, structured interviews and classroom observation were conducted. For data capture and analysis of results, the following praxiological structures (subject, context, process) were defined as beacon parameters, which within the research methodological dynamics emerged and revealed the proximity of the praxis dimensions of the sample group. In the end, the research brings denunciation and announcement, in Freire. Denunciation of the empirical epistemic focus that limits the teacher in the dialectic of his praxis. Announcement, by overcoming methodical scientific teaching, by a praxiological epistemic scientific teaching, within the framework of an authentic educational practice. Hence the need to implement transformative praxiological processes in the permanent formation of teachers, through the establishment of partnerships with educational public agencies.